A case of giant Ewing's sarcoma (EES)/primitive neuroectodermal tumor (PNET) of the cervicothoracic junction in children with incomplete paralysis of both lower limbs: Case report and literature review - Zhang, Gong-Heng; Lin, Jun-Ming; He, Zhen-Yu; Yuan, Xiao-Jun; Li, Guang; Gan, Xin-Rong; Xu, Wen-Hua; Cao, Sheng-Sheng (Frontiers in Surgery, 2023)
Background: Extraosseous Ewing's sarcoma/primary neuroectodermal tumor (EES/PNET) is a rare，malignant，small round blue cell tumor, which usually involves the larynx, kidneys, and esophagus. The most common metastatic sites are lung and bone. The incidence of epidural EES/PNET was 0.9%, and a detailed search of the PubMed literature found only 7 case reports of epidural ESS/PNET at the cervicothoracic junction in children. Case description: We report a case of epidural ESS/PNET at the cervicothoracic junction in a child with chest and back pain as the first symptom, which worsened after half a year and developed incomplete paralysis of both lower extremities and urinary incontinence. She underwent emergency surgery, chemotherapy and radiotherapy, and died of lung metastases 8 months after surgery. Conclusion: Primary epidural tumors are mostly benign, such as spinal meningiomas and neuromas. Contrary to what has been previously thought, we report a case of malignant epidural EES/PNET at the cervicothoracic junction without bone destruction; The rarity of epidural EES/PNET at the cervicothoracic junction in children has led to a lack of data, particularly on prognostic factors and recurrence patterns. Due to the difficulty of early diagnosis and high mortality, spine surgeons must explore and increase their awareness of this disease.